Angiotensin converting enzyme gene polymorphisim: Guilty or not for myocardial infarct? [Miyokard infarktüsünde suçlu anjiotensin dönüştürücü enzim gen polimorfizmi olabilir mi?] - (:unkn) unknown (My University, 2005)
Myocardial infarction is the cause behind approximately half of the total mortality in USA and many other developed countries. The most significant factors of morbidity and mortality in developed countries are myocardial infarction and coronary artery diseases. These two are multifactorial diseases affected by a mixture of genetic and external factors which are relevant for more than half of the adult population. The annual cost of the research and treatment activities aimed to cure and prevent these diseases amount to 50 to 100 billion USD. Recently we observe an increase in the intensity of research about potential genetic risk factors behind myocardial infarction. One of the most popular research topics in this respect is the investigation of a possible link between the I/D polymorphism in Angiotensin Converting Enzyme (ACE) gene and myocardial infarction. The number of researches with a focus on genetically originated risk factors of myocardial infarction is steadily increasing due to the developments in genetic and molecular biology. The identification of genetic factors behind myocardial infarction and coronary artery diseases would further facilitate the treatment of these diseases. Individuals in high-risk group could be detected and monitored for an appropriate treatment before clinical symptoms and cardiovascular complications arise. All the above-mentioned body of research is undertaken with the hypothesis that ADE gene polymorphism could play a role in the estimation of cardiovascular risks, identification of high risk groups and planning of the treatment for these groups.